Analysis of nonlinear dynamics of fully submerged payload hanging from offshore crane vessel. (1st December 2016) - Hannan, M.A.; Bai, W.
Abstract: The nonlinear dynamic responses of a fully submerged payload hanging from a fixed crane vessel are investigated numerically. A three dimensional fully nonlinear time domain model based on the boundary element method is implemented to perform the analysis. Both the payload and fixed crane vessel are considered to be periodically excited by regular waves inside the numerical tank. The motion of the payload is found to exhibit various nonlinear phenomena (for example, sub-harmonic motion, period doubling behavior) due to the presence of fixed crane vessel. Analysis tools such as the phase trajectory, bifurcation diagram and Poincaré map are used to investigate the motion characteristics of this submerged payload which is undergoing constrained pendulum motions in various scenarios. Parametric studies are also performed by varying several design parameters in order to evaluate the sensitivity of the nonlinear phenomena. Different orientations of the crane vessel and submerged payload are also considered and the results obtained reveal several important conclusions concerning the dynamic behavior of the submerged payload of offshore crane vessel during operations. It is found that change of wave motion frequency coupled with various orientations of the floating barge and submerged payload significantly alters the payload motion behavior and introduces various nonlinear phenomena. The present study can be further extended to identify the limits of the operating conditions of floating cranes and to devise techniques to control or damp the unexpected motions of the submerged payload. Highlights: The nonlinear dynamics of fully submerged payload of offshore crane barge is investigated numerically. The phase trajectories, the Bifurcation diagram and Poincaré map are applied to investigate the nonlinear motion characteristics. Nonlinear phenomena such as period doubling and sub-harmonic motions are identified. Different orientations of the floating barge and submerged payload system are responsible for the different nonlinear dynamic behavior. Low frequency motion components are found to be triggered by the natural frequency of the payload.